Financial crimes a threat to global security - Edelbacher, Max; Kratcoski, Peter C., 1936-; Theil, Michael (Advances in police theory and practice series., 2012)
Financial market reform has focused chiefly on the threats to stability arising from the risky, uncontrolled activity of the leaders of financial institutions. Nevertheless, organized crime, white-collar crime, and corruption have a huge impact on financial systems worldwide and must also be confronted if true reform is to be achieved. A collection of articles written by experts in their fields of study, Financial Crimes: A Threat to Global Security spotlights the importance of addressing the problem of illegal financial activity as part of a greater comprehensive plan for reforming the financial sector.